A computational reconstruction of Papio phylogeny using Alu insertion polymorphisms - Vallmer E. Jordan (Mobile DNA, 2018)
Abstract Background Since the completion of the human genome project, the diversity of genome sequencing data produced for non-human primates has increased exponentially. Papio baboons are well-established biological models for studying human biology and evolution. Despite substantial interest in the evolution of Papio, the systematics of these species has been widely debated, and the evolutionary history of Papio diversity is not fully understood. Alu elements are primate-specific transposable elements with a well-documented mutation/insertion mechanism and the capacity for resolving controversial phylogenetic relationships. In this study, we conducted a whole genome analysis of Alu insertion polymorphisms unique to the Papio lineage. To complete these analyses, we created a computational algorithm to identify novel Alu insertions in next-generation sequencing data. Results We identified 187,379 Alu insertions present in the Papio lineage, yet absent from M. mulatta [Mmul8.0.1]. These elements were characterized using genomic data sequenced from a panel of twelve Papio baboons: two from each of the six extant Papio species. These data were used to construct a whole genome Alu-based phylogeny of Papio baboons. The resulting cladogram fully-resolved relationships within Papio. Conclusions These data represent the most comprehensive Alu-based phylogenetic reconstruction reported to date. In addition, this study produces the first fully resolved Alu-based phylogeny of Papio baboons.